2015
DOI: 10.3923/rjet.2015.113.134
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation and Detoxification of Pulp and Paper Mill Effluent: A Review

Abstract: Presently, 50-60 m 3 of water needed to produce a ton of paper and around 240-250 chemicals have been identified in effluents, which are produced at different stages of paper making in pulp and paper industry. The pulp and paper industry is typically associated with pollution problems related to high BOD, COD, toxicity, AOX, color, suspended solids, lignin and its derivatives and chlorinated compounds. Although numerous studies have looked ways by various researchers to remove COD, BOD, color etc. of pulp and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 86 publications
(129 reference statements)
0
25
0
Order By: Relevance
“…These approaches address not only the treatment of such effluent, but also reducing its amount by implementing strategic changes to the operations within P&P mills. Wastewater treatment systems have commonly been understood to function as "end-of-pipe" solutions to environmental issues, whereas the least expensive way to treat polluted water may be to produce less of it in the first place (Stratton et al 2004;Hossain and Ismail 2015). Unit operations within P&P mill water treatment systems have been reported before and can be mentioned here (European Commission 2001;Demel et al 2003).…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…These approaches address not only the treatment of such effluent, but also reducing its amount by implementing strategic changes to the operations within P&P mills. Wastewater treatment systems have commonly been understood to function as "end-of-pipe" solutions to environmental issues, whereas the least expensive way to treat polluted water may be to produce less of it in the first place (Stratton et al 2004;Hossain and Ismail 2015). Unit operations within P&P mill water treatment systems have been reported before and can be mentioned here (European Commission 2001;Demel et al 2003).…”
mentioning
confidence: 95%
“…Since many wastewater treatment operations are exposed to sunlight, the use of algal treatment has been considered for wastewater from P&P mills. A number of researchers have shown encouraging results for such treatment (Dilek et al 1999; Tarlan et al 2002a,b;Hossain and Ismail 2015). Dilek et al (1999) demonstrated that color removal was mainly a result of metabolism, rather than biosorption.…”
Section: Bio-augmentationmentioning
confidence: 99%
See 3 more Smart Citations